The Relevance of the Concept of Imāmah in Pesantren Governance: A Study of the Leadership of Prof. Dr. K.H. Abdul Ghofur at Pondok Pesantren Sunan Drajat - Muhyidin Muhyidin; Ahmad Syairozi (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
This study examines the relevance of the concept of imamah in pesantren governance through a case study of the leadership of Prof. Dr. K.H. Abdul Ghofur at Pondok Pesantren Sunan Drajat, Lamongan, East Java. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and analysis of institutional documents. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings show that leadership practices at Pesantren Sunan Drajat embody core principles of imāmah, namely trustworthiness (amanah), justice (‘adalah), competence (kafa’ah), and consultative decision-making (syura). These principles are reflected in institutional governance, including strategic decision-making, human resource management, the strengthening of economic independence, and the development of internal and external organizational relations. Leadership is exercised not only through religious authority but also through managerial competence and ethical responsibility. This study concludes that imāmah should be understood not merely as a normative political concept, but as an ethical and practical framework for leadership applicable to contemporary pesantren governance. The research contributes to Islamic leadership studies by offering a pesantren leadership model that integrates classical Islamic values with modern governance principles.